Analysis on Financial Performance Using Du Pont System Method at PT Indofood Sukses Makmur Tbk Period 2015-2019 - Aminiar, Cica; Novitasari, Dewiana; Asbari, Masduki (Journal of Industrial Engineering & Management Research, 2020)
– The research was conduct in PT Indofood Sukses Makmur Tbk by comparing the 3 from 26 companies' food and beverage industry which is registered in the Indonesia Stock Exchange. The research using quantitative data and documentation as the data collection technique. This study was using Return on investment variable, Net Profit Margin, and Total Assets Turnover. Since 2015-2019 the results from the ROI variable are weak because it’s still under the industry average value. Meanwhile, NPM that is categorized as good enough is because it’s above the industry average. TATO variable is still categorized as not yet able to activate the effectiveness because it’s still below the average of similar industries.